An innovative operational model for companies operating bus fleets - Kruchina, Vince; Tamás, Péter; Sárközi, György Tibor; Illés, Béla (Advanced Logistic Systems - Theory and Practice, 2024)
The organization and operation of public transport have not escaped the impact of changes taking place worldwide which are driven and influenced by the rapid spread of disruptive technologies and efforts related to climate protection and sustainable development. The challenges posed by the proliferation of electric vehicles (EVs) – including electric buses (BEBs) – require new solutions and new ways of thinking, and a more holistic and innovative operating model for road transport companies using buses. In this model, the authors present a methodology for the delivery of contracted scheduled services that, as part of a systems approach, links a mixed fleet and its appropriate route plan within a data-driven circular operational model, allowing room for innovative energy solutions, the use of renewable energy sources and for satisfaction of increasingly demanding climate and sustainability requirements, all using a logistics science approach.